Knowledge And Attitude Towards Medication Safety: Study From Religion Based Hospital - Nokky Farra Fazria; Inge Dhamanti (Jurnal Kesehatan Prima, 2023)
The most prevalent patient safety incident in hospitals is medication errors. It is avoidable by a variety of safe treatment approaches known as medical safety. The topic of this research is the high rate of medical errors at 'X' Hospital Tuban in East Java, Indonesia, which accounted for 53.3% of all patient safety occurrences. The goal of this study was to investigate the impact of health workers' knowledge and attitudes on drug safety implementation at 'X' Hospital Tuban. Pharmacists, pharmaceutical technical staff, nurses, and midwives participated in an analytical cross-sectional study with 74 samples. Because of the COVID-19 outbreak, data was collected using an online survey. The survey was based on WHO's 5 Medication Safety Moments. To investigate effect identification, the Fisher's test method was applied. This survey received 87.8% response rate. The following characteristics were shared by the participants: 55.4% are nurses, 75.4% are between the ages of 26 and 36, 86.2% are female, and 36.9% work in an inpatient unit. The average score for medication safety knowledge, attitude, and implementation for each health worker was Good. The correlation coefficient (p = 0.000) between knowledge and drug safety implementation is 0.503. The correlation coefficient (p = 0.000) between attitude and drug safety implementation is 0.508. According to the findings of this study, drug safety knowledge, attitude, and implementation are all satisfactory. Medication safety knowledge and attitudes can aid in the implementation of medication safety. Suggestion for medical professionals, and 'X' Hospital Tuban is working on new pharmaceutical safety precautions.